EFFECT OF SOME LEGUMINOUS GREEN MANURE SOURCES AND NPK LEVELS ON GROWTH PARAMETERS OF MAIZE (Zea mays L.) (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2022)
The growth parameters of maize in response to incorporated legumes and NPK levels were investigated from 2015 to 2016 wet seasons at the Teaching and Research Farm of Leventist, Tumu Akko Local Government Area, Gombe State. The treatments consisted of four green manure sources (Centrosema, Lablab, Mucuna, Sesbania and control) and NPK fertilizer (0, 60 and 120 kg ha-1) laid out in a Randomized Complete Block Design (RCBD) and replicated three times. Data were collected on: plant height, number of leaves and stem girth. Data collected were subjected to Analysis of Variance (ANOVA). Means were separated using Duncan Multiple Range Test (DMRT) at 5% probability level. Results of the experiment revealed that the incorporation of Lablab significantly increased plant height; number of leaves and stem girth in all the sampling stages. Application of 60 kg NPK ha-1 gave a significant (P<0.05) increase in plant height (144.9 cm), number of leaves (11.7) and stem girth (6.4 cm) in all the sampling stages. However, further increase in NPK level from 60 kg NPK ha-1 upward had no significant effect on plant height; number of leaves and stem girth per plant. Interactions between green manure and NPK levels revealed that, incorporation of Lablab green manure and 60 kg NPK ha-1, are the most viable combinations for maximum plant growth. Based on the results obtained, application of 60 kg ha-1 N as top dress to maize grown on Lablab residue plots should be adopted by farmers in and around the study area for increased growth parameters.